Role of Smoke Stimulatory and Inhibitory Biomolecules in Phytochrome-Regulated Seed Germination of Lactuca sativa . Issue 2 (14th August 2019) - Gupta, Shubhpriya; Plačková, Lenka; Kulkarni, Manoj G.; Doležal, Karel; Van Staden, Johannes
Abstract : Karrikinolide and trimethylbutenolide from wildfire smoke regulate germination in lettuce seed by controlling phytochrome-mediated abscisic acid signaling. Abstract: The biologically active molecules karrikinolide (KAR1 ) and trimethylbutenolide (TMB) present in wildfire smoke play a key role in regulating seed germination of many plant species. To elucidate the physiological mechanism by which smoke-water (SW), KAR1, and TMB regulate seed germination in photosensitive 'Grand Rapids' lettuce ( Lactuca sativa ), we investigated levels of the dormancy-inducing hormone abscisic acid (ABA), three auxin catabolites, and cytokinins (26 isoprenoid and four aromatic) in response to these compounds. Activity of the hydrolytic enzymes α-amylase and lipase along with stored food reserves (lipids, carbohydrate, starch, and protein) were also assessed. The smoke compounds precisely regulated ABA and hydrolytic enzymes under all light conditions. ABA levels under red (R) light were not significantly different in seeds treated with TMB or water. However, TMB-treated seeds showed significantly inhibited germination (33%) compared with water controls (100%). KAR1 significantly enhanced total isoprenoid cytokinins under dark conditions in comparison with other treatments; however, there was no significant effect under R light. Enhanced levels of indole-3-aspartic acid (an indicator of high indole-3-acetic acid accumulation, which inhibits lettuce seed germination) and absence of trans-zeatin and trans-zeatin riboside (the most active cytokinins) in TMB-treated seeds might be responsible for reduced germination under R light. Our results demonstrate that SW and KAR1 significantly promote lettuce seed germination by reducing levels of ABA and enhancing the activity of hydrolytic enzymes, which aids in mobilizing stored reserves. However, TMB inhibits germination by enhancing ABA levels and reducing the activity of hydrolytic enzymes.